The Idea of a Political Settlement - Kelsall, Tim; Schulz, Nicolai; Ferguson, William D.; Hau, Matthias; Hickey, Sam; Levy, Brian (Political Settlements and Development: Theory, Evidence, Implications, 2022)
In the past, political settlements analysis (PSA) has suffered from a lack of conceptual clarity. In this chapter we provide an extended con ceptual discussion, ultimately defining a political settlement as an o ngoing agreement among a society’s most powerful groups over a set of political and economic institutions expected to generate for them a mi nimally acceptable level of benefits, which thereby ends or prevents g eneralized civil war and/or political and economic disorder. The autho rs provide an extended and nuanced defence of this definition, arguing that in contrast to most extant versions, it is both theoretically fe rtile and consistent with commonsense understandings of a political se ttlement. Universally applicable, the concept is compatible with many different and distinct political settlement theories, frameworks, and hypotheses, yet it directs attention to what should be PSA’s distincti ve contribution: an analysis of how the problem of violence shapes rul ing elites’ commitment to different sorts of development policy, or no t as the case may be. The chapter also briefly introduces a new typolo gy of political settlements, based on two novel dimensions: the social foundation and the power configuration of the settlement.